Increased NADPH oxidase activity mediates spontaneous aortic tone in genetically hypertensive rats - Lodi, Federica (2006)
NADPH oxidase is critically involved in increased blood pressure, vascular hypertrophy, inflammation and endothelial dysfunction in experimental and clinical hypertension. We hypothesized that NADPH oxidase might also play a role in the development of spontaneous aortic tone in spontaneously hypertensive rats (SHR). Wistar Kyoto rats (WKY) were used as normotensive controls. Tone was recorded under isometric conditions. NADPH oxidase activity was measured by both lucigenin luminescence and dihydroethidium fluorescence. p47phox protein was localized by immunohistochemistry. SHR (but not WKY rat) aortae showed spontaneous tone in the absence of exogenous vasoconstrictors as evidenced by a stronger relaxant effect of Ca2+-free sodium nitroprusside solution. This tone was enhanced in endothelium-denuded arteries and was inhibited by superoxide dismutase, apocynin, diphenylene iodonium and quercetin. Aortic NADPH oxidase activity, measured by both lucigenin luminescence and dihydroethidium fluorescence, was increased in SHR compared with WKY rats. Immunohistochemical analysis revealed a strong increase in p47phox expression in the medial layer in SHR. Taken together, the present results indicate that enhanced NADPH oxidase activity and, hence, NADPH driven O2- production, is involved in the spontaneous aortic tone in SHR. This was associated with an increased expression of p47phox in the medial layer of the aorta.